Sustainable Development Reserve Nascentes Geraizeiras: an ethnoconservation and resistance experience in Northern Minas Gerais - Melo, Ana Paula Gomes de; Glinfskoi Thé, Ana Paula; Morais Lima, Patrícia; Andrino de Melo, Ana Carolina (Universidade Federal Rural do Rio de Janeiro, 2021)
This article aims to analyze the path of creation of the Sustainable Development Reserve Nascentes Geraizeiras – RDSNG, in Portuguese - based on the theory of Ethnoconservation and the relationship between development, territoriality and environmental conservation on traditional peoples and communities. The RDSNG is the result of a territorial struggle experience: the resistance of the traditional Geraizeiros folk who inhabit the plateaus, slopes and valleys of the cerrado regions, in northern Minas Gerais State. Through documentary research, non-participant observation and formal and informal interviews with farmers in beneficiary communities and managers of RDSNG, it was possible to verify that striving for alternatives to the hegemonic development paradigm, these folk have been organizing, fighting and resisting in order to remain in their territories and keep their ways of life.